STRIPAK complex defects result in pseudosexual reproduction in Cryptococcus neoformans. - Patricia P Peterson; Sarah Croog; Yeseul Choi; Sheng Sun; Joseph Heitman (PLoS Genetics, 2025)
STRIPAK is an evolutionarily conserved signaling complex that coordinates diverse cellular processes across fungi and animals. In the human fungal pathogen Cryptococcus neoformans, STRIPAK was recently shown to play critical roles in maintaining genome stability and controlling both sexual and asexual development. In Cryptococcus, sexual reproduction is closely linked to virulence, and our findings demonstrate that the STRIPAK complex plays key roles in both processes. Here, we further investigate the specific roles of the STRIPAK catalytic subunit Pph22 and its regulatory partner Far8 during sexual development. We show that while pph22Δ mutants are defective in α-a sexual reproduction, exhibiting impaired meiotic progression and a failure to produce viable spores, deletion of PPH22 results in exclusive pseudosexual reproduction, with progeny inheriting nuclear genomes solely from the wild-type parent. This nuclear selection appears to result from haploinsufficiency of PPH22, in which the mutant nucleus is excluded following cell-cell fusion. Overexpression of PPG1, a related phosphatase, rescued growth and developmental defects in pph22Δ mutants, and restored the preference for α-a sexual reproduction over pseudosexual reproduction during mating, suggesting functional redundancy within the STRIPAK signaling network. Furthermore, deletion of FAR8, another component of the STRIPAK complex, also led to a high rate of pseudosexual reproduction during α-a sexual mating, reinforcing the role of STRIPAK in modulating reproductive modes in C. neoformans, possibly through regulating nuclear inheritance and meiotic progression. Transcriptomic profiling of pph22Δ and far8Δ mutants revealed dysregulation of genes involved in nuclear organization, DNA replication and repair, RNA processing, cell cycle progression, and morphogenesis, suggesting that STRIPAK disruption broadly impairs cellular programs important for faithful sexual reproduction. Together, these findings highlight the distinct contributions of STRIPAK to sexual reproduction in C. neoformans and suggest that disruptions of this complex affect genome integrity and inheritance mechanisms, with broader implications for fungal adaptation and pathogenesis.